Pengaruh Peranan Prodi Perbankan Syariah dan Kualitas Sumber Daya Manusia (SDM) terhadap Lembaga Keuangan Syariah di Kota Medan - Siti Rahmawati; Dahrani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to determine and analyze the influence of the role of islamic banking study programs and the quality of human resources on islamic financial institutions. The type of research in this thesis is quantitative research and the data used is in the form of promer data. The population used is all semester VI students of islamic banking study program, namely 58 students. Data analyze tecniques with descriptive tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The data processing process uses the SPSS version 22.0 program. The results of the study indicate hat the independent variables in this study affect the dependent variables can be seen from the model estimation showing that R Square is 54,9% and the remaining 45,1% can be influenced by other cariables outside this model.